2021
DOI: 10.3346/jkms.2021.36.e277
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report for Myopericarditis after BNT162b2 COVID-19 mRNA Vaccination in a Korean Young Male

Abstract: Mass vaccination with the Pfizer-BioNTech coronavirus disease 2019 (COVID-19) vaccine (BNT162b2) in Korea has resulted in many reported adverse effects. These side effects are the object of much scrutiny in the medical community. We report the case of a 29-year-old male who was diagnosed with myopericarditis after his second dose of Pfizer-BioNTech COVID-19 vaccine. This patient is the second recognized case of Pfizer-BioNTech COVID-19 vaccine induced myopericarditis in Korea and the first to have recovered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 , 61 , 62 , 63 , …”
Section: Resultsmentioning
confidence: 99%
“…We identified 201 studies relevant to COVID‐19 vaccination and myocarditis. Further review identified a total of 57 studies reporting cases, case series, and summated case series of COVID‐19 vaccine‐associated myocarditis 8–65 . A total of 275 cases of COVID‐19 vaccine‐associated myocarditis were reported.…”
Section: Resultsmentioning
confidence: 99%
“…As more individuals were COVID-19 vaccinated, unexpected side effects appeared, making it challenging to prevent the COVID-19. 19 20 21 22 The most common systemic adverse effects were fever, fatigue, headache, and myalgia. Younger individuals reported more local or systemic adverse effects than older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the case being reported mutually showed elevated ANA titers, but unlike Badshah et al.’s case, it was negative for all other possible autoimmune disease antibody markers ruling out the potential impact of subclinical autoimmune predisposition on vaccine-induced myopericarditis in this case. In another recent case report from Korea, a 29-year-old male was diagnosed with myopericarditis after the second dose of the Pfizer-BioNTech COVID-19 vaccine [13] . According to Kim et al., this is “the second recognized case of Pfizer-BioNTech COVID-19 vaccine-induced myopericarditis in Korea and the first to have recovered from it” [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In another recent case report from Korea, a 29-year-old male was diagnosed with myopericarditis after the second dose of the Pfizer-BioNTech COVID-19 vaccine [13] . According to Kim et al., this is “the second recognized case of Pfizer-BioNTech COVID-19 vaccine-induced myopericarditis in Korea and the first to have recovered from it” [13] . This case is similar to the case being reported in the sense that both patients revealed pericardial effusion with normal LVEF.…”
Section: Discussionmentioning
confidence: 99%